Is Congenital Syphilis Still a Problem?—A 20-Year Retrospective Study from a Northern Portuguese Level II Hospital - Figueiredo, Ana Sofia; Quintela, Carolina; Cascais, Mafalda; Calviño, Juan; Sousa, Marisa; Pereira, António; Soares, Isabel (Journal of Pediatric Infectious Diseases, 2023)
Objective The incidence of syphilis and congenital syphilis has increased in recent years according to European and United States of America official data: indeed, 2019 was the second consecutive year when the number of reported cases has increased. Syphilis is a venereal disease caused by a spirochete, Treponema pallidum. Congenital syphilis is a consequence of maternal T. palidum transmission to a fetus at any stage of maternal disease, via a transplacental pathway or during labor.Methods To investigate the incidence, characteristics, and temporal evolution of neonates with suspected congenital syphilis (proven, possible, or less likely and unlikely) or born from mothers with treated and untreated latent syphilis, we designed a retrospective and descriptive study of hospitalized neonates between 2001 and 2020, in a level II hospital located in the northern Portuguese countryside.Results We report a total of 22 neonates, 50% female. Pregnancy was unsupervised or had inadequate surveillance in 36% of cases (n = 8), in 32% (n = 7) syphilis was not treated, and in 14% (n = 3) it was inadequately treated. All neonates studied with suspected congenital syphilis were asymptomatic and all were treated with penicillin for a mean duration of 11 days. Of the 22 neonates with suspected congenital syphilis, 20 had possible congenital infection. Social vulnerability was also an important factor present in our study group.Conclusion Despite being an ancient disease, congenital syphilis is still a concern mostly due to the lack of adequate pregnancy surveillance and maternal/partner diagnosis and treatment.
Keywords: congenital syphilis; risk factors; hospitalization; treatment